Queer-Feminist Punk An Anti-Social History - Wiedlack, Maria Katharina (Zaglossus, 2015)
This history makes use of anti-social theory to take a broad and multifaceted look at queer-feminist punk-from its origins in the 1980s to its contemporary influences on the Occupy movement and Pussy Riot activism.